2022
DOI: 10.3390/metabo12060479
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics Based on GC-MS Reveals the Antipyretic Mechanism of Ellagic Acid in a Rat Model

Abstract: Ellagic acid (EA) is a polyphenol dilactone that has been reported to have antipyretic, anti-inflammatory, anti-tumor, and antioxidant activities, but the mechanism of action has not been reported. In this study, serum metabolomics was used to explore the mechanism of EA on rat fever induced by beer yeast, and to screen out marker metabolites to provide a reference for the antipyretic effect of EA. The acute fever model of male Sprague Dawley rats involved subcutaneous injection with 20% aqueous suspension of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Non-targeted metabolomics was used to identify metabolic changes in human non-alcoholic fatty liver disease after exercise intervention and revealed that alterations in amino acid metabolism may play a key role in improving fasting blood glucose concentrations in plasma [92]. Pharmacologic correlation analysis revealed the therapeutic mechanisms of ellagic acid that play antipyretic anti-inflammatory effects via inhibiting five metabolic pathways and the IKB-α/NF-κB signaling pathway [93]. Short-chain fatty acids have beneficial effects in intestinal health and as signaling molecules that affect the host metabolism.…”
Section: Mass Spectrometry-based Metabolomics For Monitoring Treatmentsmentioning
confidence: 99%
“…Non-targeted metabolomics was used to identify metabolic changes in human non-alcoholic fatty liver disease after exercise intervention and revealed that alterations in amino acid metabolism may play a key role in improving fasting blood glucose concentrations in plasma [92]. Pharmacologic correlation analysis revealed the therapeutic mechanisms of ellagic acid that play antipyretic anti-inflammatory effects via inhibiting five metabolic pathways and the IKB-α/NF-κB signaling pathway [93]. Short-chain fatty acids have beneficial effects in intestinal health and as signaling molecules that affect the host metabolism.…”
Section: Mass Spectrometry-based Metabolomics For Monitoring Treatmentsmentioning
confidence: 99%
“…Moreover, the effects of different molecules have been investigated, such as the antiviral effects of Isatis root polysaccharides against porcine reproductive and respiratory syndrome virus [39] or the possible anticoagulant and antithrombotic effects of the venom of the snake Deinagkistrodon acutus [40]. Potential pharmacological effects were also found by Xie et al who associated the antipyretic mechanism to ellagic acid in rats [41,42]. Additionally, a blood deficiency rat model was used to investigate the hematopoietic and antioxidant effects of Maoji Jiu medicinal wine on metabolism [43].…”
mentioning
confidence: 99%